The Effect of Using the Buffer Solution Material Module on the Learning Outcomes of Class XI Science Students at MAS PSA Sulit Air - Syukri Hamid; Iswendi Iswendi (Universitas Negeri Padang, 2023)
ABSTRACT The learning process carried out at MAS PSA Sulit Air still uses the lecture method and the learning resources used are in the form of textbooks, and have never used learning modules, thus causing students to be less active in the learning process. While in the 2013 curriculum it is said that during the learning process students must be actively involved. Efforts to make students actively involved in the learning process is to use teaching materials in the form of learning modules. This study aims to reveal the effect of using the buffer solution module on the learning outcomes of class XI IPA students at MAS PSA Sulit Air. Type of research is a quasi-experimental with a non-equivalent control group design. The research instrument used was a test of student learning outcomes in the form of 25 objective questions that had been tested. The data from the test results show that the data is normally distributed and homogeneous, so that hypothesis testing can be carried out with the t-test. From the results of the t-test, obtained Tcount>Ttable at a significant level of 0.05, it is stated that H1 is accepted. This means that the experimental class student learning outcomes are significantly higher than the control class. The results showed that the use of the buffer solution material module could improve student learning outcomes in class XI IPA at MAS PSA Sulit Air.